Searching for a consensus five-factor model of the Positive and Negative Syndrome Scale for schizophrenia - Wallwork, R.S.; Fortgang, R.; Hashimoto, R.; Weinberger, D.R.; Dickinson, D. (Schizophrenia research, 2012)
Although the developers of the Positive and Negative Syndrome Scale (PANSS) grouped items into three subscales, factor analyses indicate that a five-factor model better characterizes PANSS data. However, lack of consensus on which model to use limits the comparability of PANSS variables across studies. We counted “votes” from published factor analyses to derive consensus models. One of these combined superior fit in our Caucasian sample (n=458, CFI=.970), and in distinct Japanese sample (n=164, CFI=.964), relative to the original three-subscale model, with a sorting of items into factors that was highly consistent across the studies reviewed.